ChemInform Abstract: An Efficient Route to N‐Monosubstituted Guanidino‐Lactams. Issue 7 (January 2016) - Tommasi, Sara; Zanato, Chiara; Carabeo, Rey; Mangoni, Arduino A.; Dall'Angelo, Sergio; Zanda, Matteo
Abstract: The preparation of a range of N‐alkyl substituted N, N′‐bis‐Boc‐pyrazole‐1H‐carboxamidines as guanylating agents from the corresponding alkyl alcohols is described which may contain various functional groups.